2019
DOI: 10.1002/pen.25265
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Microcellular Morphology Evaluation in ABS‐Foamed Composites Developed Using Step‐Wise Depressurization Foaming Process

Abstract: In this article, the fabrication of bimodal type of cellular structures and multimodal type of cellular structures of acrylonitrile–butadiene–styrene foams has been reported using solid‐state batch foaming process by distinct, stepwise depressurization technique. Each depressurization step induces a distinct nucleation phenomenon, which leads to the development of multimodal cellular microstructures. The significance of crucial process parameters, which includes saturation pressure, holding pressure, holding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…For this purpose, polymer foams with BCS are a sort of promising materials, which could be used in fields of packing, chemistry industry and construction. [ 30 ] Up to now, some effective approaches have been carried out to prepare polymer foams with BCS, including two‐step depressurization, multiphase polymer melt‐blending, the synergistic effect of cooling and depressurization, as well as co‐blowing agent method. Salerno et al [ 31 ] prepared porous scaffolds of polycaprolactone (PCL)/hydroxyapatite nanocomposites with BCS via two‐step depressurization foaming method and the results demonstrated that the control of the intermediate pressure and thermal history was necessary to design porous PCL scaffolds with BCS.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, polymer foams with BCS are a sort of promising materials, which could be used in fields of packing, chemistry industry and construction. [ 30 ] Up to now, some effective approaches have been carried out to prepare polymer foams with BCS, including two‐step depressurization, multiphase polymer melt‐blending, the synergistic effect of cooling and depressurization, as well as co‐blowing agent method. Salerno et al [ 31 ] prepared porous scaffolds of polycaprolactone (PCL)/hydroxyapatite nanocomposites with BCS via two‐step depressurization foaming method and the results demonstrated that the control of the intermediate pressure and thermal history was necessary to design porous PCL scaffolds with BCS.…”
Section: Introductionmentioning
confidence: 99%